Understanding Brand Switching Intention: The Role of Consumer Animosity, Religiosity, and Perceived Economic Risk Mediated by Customer Engagement - Ahmad Rasyiddin; Maman Sulaeman; Diksi Metris; Sindi Elvira Sagita; Yoan Yolanda (Fakultas Ekonomi Universitas Garut, 2026)
Geopolitical conflicts have historically reshaped consumer behavior in profound ways, as powerfully evidenced by the widespread product boycotts observed in Muslim-majority countries following the escalation of the Middle East conflict in October 2023. This study examines how consumer animosity, Islamic religiosity, and perceived economic risk influence brand switching intention toward alternative products, with customer engagement as a mediating variable. Data were collected from 397 marketplace users in Indonesia via structured questionnaire and analyzed using PLS-SEM. All three independent variables significantly and positively influence both customer engagement and brand switching intention, with customer engagement partially mediating all three relationships. These findings offer two notable contributions: the empirical validation of customer engagement as a mediator across all three antecedents a pathway not previously tested and the Indonesian digital marketplace context, which provides an empirical anchor that existing literature has insufficiently addressed.